Eccentric Exercise and Delayed Onset of Muscle Soreness (DOMS) – an Overview - Seidel, E. J.; Rother, M.; Hartmann, J.; Rother, I.; Schaaf, T.; Winzer, M.; Fischer, A.; Regenspurger, K. (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2012)
The aim of this literature based analysis was to identify the reasons, kinetics and intervention possibilities of delayed onset of muscle soreness (DOMS).Literature analysis via common online search engines PubMed and MedLine supported by a clinical study with multiple evaluation points (before exercise, at 12, 13, 14, 16, 20 and 24 h after exercise and subsequently in 12 h intervals up to 156 h post exercise) to investigate pain kinetics. The study investigated the effect of walking down stairs with a total altitude of 300–400 m depending on body weight on muscle pain in 48 healthy subjects. Subjects rated pain on a 10 point categorical Likert scale.DOMS is almost exclusively caused by eccentric muscle contractions. The pain starts after 6–8 h and peak between 24–48 h after the exercise and can stay up to one week. There are numerous treatment methods for DOMS such as: medical, nutritional and physical interventions. Several methods were found to alleviate DOMS and/or to reduce the inflammation parameters, unfortunately, most of them only after 24–48 h. But the results for most approaches are still controversial. Use of non-steroidal anti-inflammatory drugs might initially reduce pain but on the expense of even a delay in recovery.Many treatment options were found that reduced inflammation and pain significantly. However, none of these treatments were found consistently to support or accelerate the structural and functional muscle regeneration. Regular physical training to condition the muscles to unfamiliar eccentric exercise appears to be the best preventive approach. Additional eccentric training during rehabilitation is beneficial for patients with reduced cardio-pulmonary capacity.
Keywords: pain; rehabilitation; physical therapies; eccentric exercise; muscle soreness